Polydiacetylene-Na+Nanoribbons for Naked Eye Detection of Hydrogen Chloride Gas - Kingchok S. (2023)
Polydiacetylene (PDA) is a class of color-responsive materials that has been utilized in advanced sensing applications. The development of PDA as an acid sensor often requires structural modification of the headgroup, involving time-consuming synthetic processes. In this study, we have found a versatile route for achieving acid response of PDA materials via a sol-gel method. Simple mixing of sodium hydroxide and a commercial diacetylene monomer, 5,7-hexadecadiynoic acid (HDDA), in an aqueous solution leads to supramolecular assembly to form nanoribbons and consequently gelation under ambient conditions. Interestingly, solid-state sensors of poly(HDDA-Na+) fabricated from the gels exhibit a colorimetric response to hydrogen chloride (HCl) gas. The red-to-orange color transition takes place at an HCl gas concentration as low as 400 ppm. The response time at 1300 ppm of HCl gas, the lowest lethal concentration causing fatality of a human, is within 1 min. The quick response of the poly(HDDA-Na+) sensor allows visual detection of HCl gas and provides sufficient time to take safety precautions. This sol-gel process is simple, showing potential for large-scale production. Our study also offers a development path for PDA materials that expands their applications as acid sensors.